Evaluasi Pertumbuhan dan Hasil Beberapa Genotipe Cabai (Capsicum annuum L.) untuk Toleransi terhadap Cekaman Aluminium - Purnomo, D. Wasgito; Purwoko, Bambang S.; Yahya, Sudirman; Sujiprihati, Sriani; Mansur, Irdika (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
The aim of this research was to evaluate growth and yield in response to aluminum (Al) stress in several genotypes of chilli (Capsicum annuum L.). The research was conducted in University Farm of IPB, Cikabayan, Bogor from February to August 2006. Ultisol soils from Gajrug (Lebak, Banten) in polybag with pH 4.2, Al-dd 30.08 me/ 100 g and Al-saturated 83.81% was used in this experiment. Eight genotypes of chilli (4 tolerant and 4sensitive) were tested on two different conditions, in media without Al-stress condition (Al-saturated 0.77%) and wich Al-stress (Al-saturated 60.85%). Characters observed were plant height, shoot dry-weight, total number of fruits per plant, number of fruit harvested per plant, fruit dimension (length and diameter), fruit weight harvested per plant, and weight of each fruit. The results showed that there were differences of response to Al-stress among genotypes on the study. PBC 619 and Jatilaba were selected as tolerant genotypes, while Cilibangi 3 and Helm were sensitive. This evaluation of agronomic characters for tolerant and sensitive to Al-stress appeared very consistent with root bioassay results. Based on this result, the root bioassay method can be used to select chili genotypes for Al-stress tolerance. Key words: Growth and yield evaluation, aluminum stress, Capsicum annuum, ultisol soil.